1980
DOI: 10.1001/archsurg.1980.01380110119019
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Asymptomatic Ulcerating Carotid Lesions

Abstract: One hundred twenty eight cervical carotid arteriograms were twice viewed by three readers for the evaluation of atherosclerotic disease at the carotid bifurcation. Stenoses were estimated using calipers to the nearest 5% and lesions were qualitatively characterized as smooth, irregular, or ulcerated. The intraobserver correlation coefficient between estimates of percent stenosis was .94 overall and .98 for the internal carotid artery. The average intraobserver variability in estimating percent stenosis was 5.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The distribution of patients by age and sex is detailed in Table 1. There were more females (19) than males, with a mean age of 61 years. The right hemisphere was involved 17 times, the left, 15.…”
Section: Materials and Methods Patient Selectionmentioning
confidence: 99%
“…The distribution of patients by age and sex is detailed in Table 1. There were more females (19) than males, with a mean age of 61 years. The right hemisphere was involved 17 times, the left, 15.…”
Section: Materials and Methods Patient Selectionmentioning
confidence: 99%
“…Kroener et al 30 found a more benign prognosis for asymptomatic ulcerated plaques with minor stenosis. In a retrospective review of 91 ulcerated plaques, only one stroke occurred in 79 patients in a mean follow-up of 36 months (range 1-7 years).…”
Section: Ulcerated Plaques and Prognosismentioning
confidence: 97%
“…They recommended prophylactic surgery for the large ulcers. Yet in another recent retrospective study by Kroener et al, 26 76 patients with 87 asymptomatic shallow ulcers or ulcerated plaques followed over a mean of 3 years yielded only 4 TIAs overall, 1 stroke in the 55 patients with 63 small ulcers, and none in the 21 with 24 large ulcers. Based on the stroke rate of 1% over a seven year period, the authors concluded endarterectomy is not justified for asymptomatic carotid bifurcation ulcerations.…”
mentioning
confidence: 93%